2017
DOI: 10.1080/09602011.2017.1333012
|View full text |Cite
|
Sign up to set email alerts
|

Detection of text-based social cues in adults with traumatic brain injury

Abstract: Objectives: Written text contains verbal immediacy cues - word form or grammatical cues that indicate positive attitude or liking toward an object, action, or person. We asked if adults with moderate-severe traumatic brain injury (TBI) would respond to these cues, given evidence of TBI-related social communication impairments. Methods: 69 adults with TBI and 74 healthy comparison (HC) peers read pairs of sentences containing different types of immediacy cues (e.g., speaker A said “these Canadians” vs. B said… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 64 publications
(84 reference statements)
0
5
0
Order By: Relevance
“…Cognitive-communicative difficulties after TBI typically affect socio-pragmatic aspects of communication more so than linguistic aspects. Emerging research has suggested that people with TBI may miss subtle social cues written in text (Turkstra, Duff, Politis, & Mutlu, 2019). However, the participants in this study identified cognitive fatigue, emotional overload, and planning difficulties as more of a challenge for them than the writing of tweets.…”
Section: The Dark Side Of Twitter For People With Tbimentioning
confidence: 64%
“…Cognitive-communicative difficulties after TBI typically affect socio-pragmatic aspects of communication more so than linguistic aspects. Emerging research has suggested that people with TBI may miss subtle social cues written in text (Turkstra, Duff, Politis, & Mutlu, 2019). However, the participants in this study identified cognitive fatigue, emotional overload, and planning difficulties as more of a challenge for them than the writing of tweets.…”
Section: The Dark Side Of Twitter For People With Tbimentioning
confidence: 64%
“…Analysis of variance (ANOVA) revealed a significant between-groups difference on all neuropsychological measures (see Table 1), no significant sex-based differences on any measure (all p -values > .05), and no significant interaction of group and sex (all p -values > .05). Additionally, a subset of the participants whose data was included in the current paper has shown impaired mentalizing in other tasks, such as identifying speaker preferences expressed in text-based messages (35) and identifying emotion in facial affect recognition tasks (36). These impairments, coupled with the group differences we have identified in neuropsychological measures, suggest that the population that is included in the current study will have impaired mentalizing ability and, thus, not use robot social gaze cues to successfully infer the mental state of their robot, as predicted by our study hypothesis.…”
Section: Methodsmentioning
confidence: 99%
“…However, many of these individuals have cognitive disabilities that may affect social media use. Individuals with TBI may experience changes in memory, social perception, and social communication [ 10 ] and thus may find it more challenging to perceive text-based social cues in social media than cues present in face-to-face communication [ 11 , 12 ]. TBI-related memory and learning disabilities may make it difficult to keep up with evolving requirements of regularly updating social media platforms [ 3 ], and reduced attention may create challenges parsing critical information from cluttered news feeds [ 13 ].…”
Section: Introductionmentioning
confidence: 99%